2020
DOI: 10.3389/fendo.2020.00444
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and Metabolic Effects of Low-Calorie and Non-Calorie Sweeteners

Abstract: Since excessive sugar consumption has been related to the development of chronic metabolic diseases prevalent in the western world, the use of sweeteners has gradually increased worldwide over the last few years. Although low-and non-calorie sweeteners may represent a valuable tool to reduce calorie intake and prevent weight gain, studies investigating the safety and efficacy of these compounds in the short-and long-term period are scarce and controversial. Therefore, future studies will need to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 213 publications
(282 reference statements)
0
25
0
4
Order By: Relevance
“…In the current study, NSSs were found in one-fifth of the assessed 73,885 products, which is less than the 55% reported in a study in Chile [49], but much higher than the value found in studies conducted in Colombia, Brazil, Australia, and Hong Kong, where the proportion of products containing NSSs was no higher than 16% [18,19,50,51]. NSSs are usually added to products as (in part) a replacement for added sugars in response to emerging sugar reduction policies and increasing consumer concern regarding added sugars [52], but their impact on health remains controversial [53]. It was reported by WHO that replacing sugars with NSSs in the short term results in reductions in body weight, but may be associated with increased risk of type 2 diabetes, cardiovascular diseases, and mortality in the longer term [54].…”
Section: Discussionmentioning
confidence: 94%
“…In the current study, NSSs were found in one-fifth of the assessed 73,885 products, which is less than the 55% reported in a study in Chile [49], but much higher than the value found in studies conducted in Colombia, Brazil, Australia, and Hong Kong, where the proportion of products containing NSSs was no higher than 16% [18,19,50,51]. NSSs are usually added to products as (in part) a replacement for added sugars in response to emerging sugar reduction policies and increasing consumer concern regarding added sugars [52], but their impact on health remains controversial [53]. It was reported by WHO that replacing sugars with NSSs in the short term results in reductions in body weight, but may be associated with increased risk of type 2 diabetes, cardiovascular diseases, and mortality in the longer term [54].…”
Section: Discussionmentioning
confidence: 94%
“…Recommended water intake was at least 2.5 lt/day. To avoid micronutrient deficiencies, mineral and vitamin supplements were recommended and only erythritol or steviol glycosides were allowed as sweeteners [28]. The maximal duration of the first two phases (ketosis phases) was 3 months (T1).…”
Section: Nutritional Interventionmentioning
confidence: 99%
“…A recent publication showed that maternal NNS intake during pregnancy was associated with increased childhood body mass index (BMI) z-score and body fat from birth to teenage years [28]. Studies suggest that NNS may contribute to the development of metabolic syndrome and insulin resistance [29][30][31]. A systematic review and meta-analysis published in 2017 found that consumption of NNS was associated with hypertension, type 2 diabetes and cardiovascular events [30].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis published in 2017 found that consumption of NNS was associated with hypertension, type 2 diabetes and cardiovascular events [30]. LNCS also interfere with gut microbiota composition [29,31,32].…”
Section: Introductionmentioning
confidence: 99%